Supported late transition metal catalyst for ethylene polymerization and in-situ grafting as well as preparation method and application thereof
By using a supported transition metal catalyst and a radical initiator, and combining with spray drying, the catalyst is prepared, the problems of uneven grafting and low grafting rate of polyethylene are solved, and efficient and uniform grafting reaction and simplified preparation process are achieved.
Patent Information
- Application Number
- CN202311291843.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2043-10-08
AI Technical Summary
The existing polyethylene grafting methods have problems such as uneven grafting, low grafting rate, numerous operations and unfriendly environment.
A supported transition metal catalyst is used, which introduces a radical initiator during the preparation process and is prepared by spray drying. The catalyst has good particle shape and adjustable particle size, achieving uniformity and high efficiency of ethylene polymerization and in-situ grafting.
The uniformity and efficiency of the grafting reaction are achieved, the amount of free radical initiator is reduced, the grafting rate is improved, the preparation process is simplified, and the bulk density of the polymer is increased.
Smart Images

Figure BDA0004481903250000032 
Figure BDA0004481903250000101 
Figure BDA0004481903250000102
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyolefin catalysts, and in particular to a supported late transition metal catalyst for olefin polymerization and in-situ grafting, and a preparation method and application thereof. Background Art
[0002] Polyethylene is the most common general-purpose plastic, but due to its complete lack of polarity, its application is subject to certain limitations. In order to expand its scope of application and improve its processing and performance deficiencies, it is usually necessary to carry out processing modification to introduce polar groups into its molecular chain.
[0003] Catalysts are the core technology of the polyolefin industry. Late transition metals usually refer to metal elements whose catalytic active centers are in the right half of the transition metal group of the periodic table (such as Ni, Pd, Pt, Co, Fe, Ru, Rh, Cu). In 1995, Brookhart et al. reported a class of late transition metal catalysts with unique "chain walking" characteristics. They can produce branched polyethylene without adding comonomers, and can control the branching degree of the polymer by controlling temperature and pressure. This has attracted great attention. After loading, it can not only maintain its catalytic properties, improve polymer morphology, and increase bulk density, but also adapt to existing slurry polymerization process equipment.
[0004] The commonly used polyethylene grafting methods are: 1. Melt grafting. This is the most commonly used and most researched chemical grafting method. The polyethylene in a molten state is grafted with the grafting monomer in an extruder under the action of an initiator; 2. Solution grafting. This refers to dissolving polyethylene, polar monomers and initiators in a reaction medium for grafting reaction; 3. Solid phase grafting. This is to place polyethylene powder directly with initiators, grafting monomers, surfactants, etc. for contact reaction; 4. Radiation grafting. This method uses high-energy gamma rays or ultraviolet rays as radiation energy. The irradiated polyethylene produces free radicals, which are then polymerized with the grafting monomer to obtain a grafted free radical initiator (Plastics Science and Technology, 2005 (2): 42-46). The above methods all involve secondary reactions of the finished polyethylene to obtain grafted polyethylene.
[0005] Among them, the melting method requires large equipment investment, and the gel content is high due to the high preparation temperature; the solid phase grafting method has many advantages such as simple operation, short reaction time, no need for large equipment and therefore low investment, no need for reaction medium and therefore no need for solvent recovery and other operation steps, and has high practical value. However, this method also has disadvantages: the reaction is a heterogeneous system and a local modification method, so it is prone to problems such as uneven grafting and low grafting rate. The radiation method also has such problems; and although the solution method is a homogeneous system and can obtain uniform grafted products, the products need to be dried and separated, which requires many operations and is not environmentally friendly. Summary of the invention
[0006] Based on this, the present invention provides a late transition metal catalyst for ethylene polymerization and in-situ grafting and a preparation method thereof, wherein the catalyst introduces a free radical initiator during the preparation process, and the preparation process is relatively simple, wherein the late transition metal catalyst is responsible for catalyzing ethylene polymerization, wherein the free radical initiator is uniformly dispersed in the polyethylene powder, and then the free radical initiator initiates the polar monomer to be grafted on the polyethylene, and the grafting reaction is more uniform, the amount of the free radical initiator is small, and the grafting rate efficiency is higher, and due to the special "chain walking" behavior of the late transition metal catalyst, the branching degree and molecular weight of the polyethylene can be regulated by adjusting the catalyst ligand structure, the polymerization temperature and pressure, etc., so as to polymerize the polyethylene that is easier to be polarly grafted, and the adjustability is high; on the other hand, the catalyst is prepared by a spray drying method, and the catalyst not only has a good particle shape, but also can adjust the catalyst particle size according to the use requirements, thereby improving the grafting rate. The present invention uses the catalyst to directly obtain grafted polyethylene by a one-step method, and the product does not need to be dried and separated, and the polymer powder has a high bulk density, thereby simplifying the preparation process of grafted polyethylene.
[0007] The first aspect of the present invention is to provide a supported late transition metal catalyst, comprising a blended component and / or reaction product of the following raw materials: a carrier, a late transition metal catalyst, an activator and a free radical initiator, wherein the activator is an organic aluminum compound.
[0008] According to the present invention, the carrier can be selected from a wide range. In a preferred embodiment of the present invention, the carrier is selected from an inorganic oxide carrier, preferably silicon oxide and / or aluminum oxide, and more preferably silicon dioxide.
[0009] According to the present invention, preferably, the particle size of the carrier is 0.01 to 5 μm, preferably 0.01 to 2 μm.
[0010] According to the present invention, the free radical initiator can be selected in a wide range. In a preferred embodiment of the present invention, the free radical initiator is selected from at least one of azo and peroxide initiators, preferably selected from at least one of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, diisobutyl peroxydicarbonate, azobisisobutyronitrile and azobisisoheptylonitrile.
[0011] According to the present invention, the organoaluminum compound can be selected in a wide range. In a preferred embodiment of the present invention, the organoaluminum compound is AlR n X (3-n) or contains A compound of the structure, wherein R is an alkyl group having 1 to 10 carbon atoms, X is a halogen, and n is an integer of 1 to 3; more preferably, the organoaluminum compound is selected from at least one of trimethylaluminum, triethylaluminum, methylaluminoxane, diethylaluminum monochloride, ethylaluminum dichloride, tri-n-butylaluminum, triisobutylaluminum, sesquimethylaluminum chloride, and sesquiethylaluminum chloride.
[0012] According to the present invention, the late transition metal catalyst can be selected from a wide range. For the above-mentioned late transition metal catalyst, the present invention can be obtained by the method in the prior art, such as the diamine complex recorded in CN111116787A, the diimine metal complex recorded in CN112745362A, the late transition metal catalyst in CN114478868A, CN104059175A, CN104059175B, etc.
[0013] In the present invention, the above-mentioned late transition metal catalyst is prepared based on the method disclosed in references Polymers 2018, 10, 2073-4360, Macromolecules 2014, 47, 3325-3331, Angew. Chem., Int. Ed. 2004, 43, 1821-1825, J. Am. Chem. Soc. 2014, 136, 7213 7216, etc. The relevant contents disclosed in the above-mentioned documents can all be introduced into the present invention as a reference and will not be repeated here.
[0014] In a preferred embodiment of the present invention, the late transition metal catalyst has a structure as shown in formula (I):
[0015]
[0016] Formula (I);
[0017] In formula (I), R1 to R2 are each selected from hydrogen or an alkyl group or an aryl group having 1 to 20 carbon atoms, preferably each selected from at least one of hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms;
[0018] R3 to R8 are each selected from hydrogen or an alkyl or aryl group having 1 to 20 carbon atoms, preferably each selected from at least one of hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms;
[0019] X1 and X2 are halogen, preferably each selected from at least one of chlorine, bromine and iodine;
[0020] M is Fe, Co or Ni.
[0021] In a preferred embodiment of the present invention, based on the total mass of the supported late transition metal catalyst as 100wt%, the content of the late transition metal M in the supported late transition metal catalyst is 0.1-5wt%, for example, it can be any value among 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or the range between any two values, preferably 0.3-3wt%.
[0022] In a preferred embodiment of the present invention, based on the total mass of the supported late transition metal catalyst as 100wt%, the content of the free radical initiator is 10-60wt%, for example, it can be any value among 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt% or the range between any two values, preferably 20-40wt%.
[0023] In a preferred embodiment of the present invention, the molar ratio of aluminum to the late transition metal element M in the organic aluminum compound is (5-500):1, for example, it can be any ratio of 5:1, 10:1, 50:1, 100:1, 300:1, 500:1 or a range between any two ratios, preferably (20-200):1.
[0024] In a more preferred embodiment of the present invention, based on the total mass of the supported late transition metal catalyst as 100wt%, the content of the late transition metal M in the supported late transition metal catalyst is 0.1-5wt%, preferably 0.3-3wt%, and / or the content of the free radical initiator is 10-60wt%, preferably 20-40wt%; the molar ratio of aluminum to the late transition metal element M in the organic aluminum compound is (5-500):1, preferably (20-200):1.
[0025] In a preferred embodiment of the present invention, the average particle size of the supported post-transition metal catalyst is 7 to 100 μm. The inventors of the present invention have found through research that, based on the catalyst formulation of the present invention (i.e., carrier, post-transition metal catalyst, activator and free radical initiator, wherein the activator is an organic aluminum compound), by further adjusting the average particle size of the supported post-transition metal catalyst, the grafting rate of the grafted polyethylene can be adjusted while maintaining a certain polymerization activity. Within the preferred average particle size range of the present invention, a grafted polyethylene with a high grafting rate can be obtained. More preferably, the average particle size of the supported post-transition metal catalyst is 8 to 30 μm, which can further improve the grafting rate. Further more preferably, the average particle size of the supported post-transition metal catalyst is 8 to 20 μm; most preferably, the average particle size of the supported post-transition metal catalyst is 8-15 μm, and under the condition of a further lower average particle size, the grafted polyethylene has a further higher grafting rate.
[0026] In a more preferred embodiment of the present invention, the late transition metal catalyst in the supported catalyst formula is selected from Catalyst 1 in the example. The structure of Catalyst 1 makes it easier for the polymer chain to undergo "chain walking" during the polymerization process, thereby increasing the degree of polymer branching and achieving a higher grafting rate.
[0027] According to the present invention, in order to further improve the uniformity of the particle size of the obtained grafted polyethylene and make the particle size distribution narrower, in a preferred embodiment of the present invention, the particle size distribution of the supported late transition metal catalyst is less than 2, more preferably less than 1.5.
[0028] In the present invention, the particle size refers to the average particle size, that is, the equivalent diameter of the largest particle when the cumulative distribution is 50% in the particle size distribution curve (d 50 ). Particle size distribution refers to the diameter distance, that is, (d 90 -d 10 ) / d 50 ), which describes how broad the particle distribution is.
[0029] The second aspect of the present invention is to provide a method for preparing the supported late transition metal catalyst according to the first aspect, comprising the following steps:
[0030] (1) dispersing components including the late transition metal catalyst, an activator, a carrier, and a free radical initiator in an organic solvent to form a slurry;
[0031] (2) spray drying the slurry obtained in step (1) to obtain the supported late transition metal catalyst.
[0032] According to a preferred embodiment of the present invention, the preparation of the slurry in step (1) comprises: dissolving the free radical initiator, the late transition metal catalyst, and the activator in an organic solvent and then adding the carrier; more preferably, first dissolving the free radical initiator, the late transition metal catalyst, and the activator in an organic solvent, adding the carrier at 20-45° C. and mixing for 2-12 hours. More preferably, the dissolution condition is constant temperature at 20-40° C. for 0.5-3 hours.
[0033] According to a specific embodiment of the present invention, in the step (2): the spray drying can adopt the spray drying equipment and process conditions commonly used in the art. According to a preferred embodiment of the present invention, the spray drying conditions in the step (2) are: inlet temperature 50-200°C, outlet temperature 30-150°C.
[0034] According to the present invention, the particle size of the catalyst obtained can be adjusted by the air flow rate of the spray drying nozzle. According to a preferred embodiment of the present invention, the air flow rate of the spray drying nozzle in step (2) is 10-50m 3 / h, more preferably 21-50m 3 / h, and more preferably 26-50m 3 / h.
[0035] In a preferred embodiment of the present invention, the organic solvent is selected from at least one of alkanes, halogenated alkanes, aromatic hydrocarbons, heterocyclic compounds, ethers, ketones, and esters, and more preferably selected from at least one of pentane, hexane, heptane, dichloromethane, chloroform, benzene, toluene, chlorobenzene, chlorotoluene, tetrahydrofuran, acetone, ether, and ethyl acetate.
[0036] In a preferred embodiment of the present invention, the amount of the organic solvent used is 5 to 100 mL, preferably 10 to 50 mL, relative to 1 g of the carrier.
[0037] According to the present invention, the amount of each raw material can be selected in a wide range. In a preferred embodiment of the present invention, the amount of the late transition metal catalyst is 0.01-1 part, the amount of the activator is 0.1-30 parts, and the amount of the free radical initiator is 0.02-10 parts, relative to 1 part of the carrier, by mass. More preferably,
[0038] In parts by mass, relative to 1 part of the carrier, the amount of the late transition metal catalyst is 0.05-0.5 parts, the amount of the activator is 0.3-10 parts, the amount of the free radical initiator is 0.1-3 parts, and more preferably the amount of the free radical initiator is 0.8-3 parts.
[0039] The third aspect of the present invention is to provide an application of the supported late transition metal catalyst described in the first aspect or the supported late transition metal catalyst prepared by the preparation method described in the second aspect in olefin polymerization, preferably in ethylene polymerization and in-situ grafting.
[0040] In a preferred embodiment of the present invention, the use of the supported late transition metal catalyst in olefin polymerization (i.e., ethylene polymerization and in-situ grafting method) comprises:
[0041] 1) contacting ethylene with the supported late transition metal catalyst to perform ethylene polymerization reaction to obtain polyethylene powder containing a free radical initiator, wherein the free radical initiator is uniformly dispersed in the polyethylene powder;
[0042] 2) contacting the polar monomer for grafting with the polyethylene powder containing the free radical initiator obtained in 1) so that the free radical initiator initiates in-situ grafting of the polar monomer on the polyethylene.
[0043] Preferably, the polar monomer is a compound containing a double bond and a polar group, more preferably at least one of acrylic acid and its derivatives or esters, maleic anhydride or esters, maleate, alkenyl bisphenol A ether, acrylonitrile, styrene and its homologues, and glycidyl methacrylate.
[0044] The methods of ethylene polymerization and in-situ grafting in the present invention include but are not limited to ethylene slurry polymerization and grafting reaction.
[0045] For example, in ethylene slurry polymerization and grafting reaction, the conditions for ethylene polymerization reaction include:
[0046] The temperature is 30-90° C., the reaction time is 0.5-3 hours, the pressure is 0.1-5 MPa, and the amount of the supported transition metal catalyst is 20-500 mg; preferably, the reaction is carried out in the presence of alkyl aluminum or methyl aluminoxane.
[0047] The alkyl aluminum can be selected from at least one of sesquiethylaluminum chloride, triethylaluminum, tri-n-hexylaluminum, tri-isobutylaluminum, and tri-n-octylaluminum, and / or the amount of the alkyl aluminum or methylaluminoxane is 5-1000 mol relative to 1 mol of the metal element content in the supported late transition metal catalyst. The alkyl aluminum or methylaluminoxane has the following functions: (1) as an impurity remover, removing water and oxygen in the reaction process to avoid interference with the polymerization reaction; and (2) stimulating the catalyst to carry out the polymerization reaction.
[0048] The conditions of the ethylene polymerization reaction are such that the content of the free radical initiator in the obtained polyethylene powder containing the free radical initiator is 0.1-10 wt %.
[0049] As an example, during ethylene slurry polymerization and grafting reaction, the conditions for the in-situ grafting reaction include:
[0050] The temperature is 80-150°C, the reaction time is 2-8h, the pressure is 1-5MPa, and the mass ratio of polyethylene powder containing free radical initiator to polar monomer is 100-3:1.
[0051] The present invention provides a late transition metal catalyst for ethylene polymerization and in-situ grafting and a preparation method thereof. The catalyst introduces a free radical initiator during the preparation process, and the preparation process is relatively simple. First, the late transition metal catalyst is responsible for catalyzing ethylene polymerization. At this time, the free radical initiator is evenly dispersed in the polyethylene powder, and then the free radical initiator initiates the polar monomer to be grafted on the polyethylene. The grafting reaction is more uniform, the amount of free radical initiator is small, and the grafting rate efficiency is higher. Due to the special "chain walking" behavior of the late transition metal catalyst, the branching degree and molecular weight of polyethylene can be regulated by adjusting the catalyst ligand structure, polymerization temperature and pressure, etc., so as to polymerize polyethylene that is easier to polar graft, and the adjustability is high; on the other hand, the catalyst is prepared by a spray drying method, and the catalyst not only has a good particle shape but also can adjust the catalyst particle size according to the use requirements, thereby improving the grafting rate. The catalyst can be used to directly obtain grafted polyethylene by a one-step method, the product does not need to be dried and separated, the polymer powder has a high bulk density, and the preparation process of grafted polyethylene is simplified.
[0052] Compared with the prior art, the present invention has the following advantages:
[0053] (1) The present invention provides a supported late transition metal catalyst for ethylene polymerization and in-situ grafting. A free radical initiator is added during the loading process, and after initiating ethylene polymerization, the free radicals can be evenly dispersed in the polyethylene, thereby initiating in-situ polar monomer grafting, and polar grafted polyethylene can be directly obtained in one step;
[0054] (2) The present invention provides a supported late transition metal catalyst for ethylene polymerization and in-situ grafting. A free radical initiator is added during the loading process. After initiating ethylene polymerization, the free radicals can be evenly dispersed inside the polyethylene, thereby initiating in-situ polar monomer grafting. The amount of initiator used is small, the grafting reaction is more uniform, and the grafting rate is higher.
[0055] (3) The catalyst prepared by the supported late transition metal catalyst provided by the present invention is used for olefin polymerization to obtain a resin powder having good particle morphology and high bulk density. The product does not need to be dried and separated, and can be used in a slurry polymerization process.
[0056] (4) The present invention uses a supported late transition metal catalyst to catalyze ethylene polymerization. Its special "chain walking" behavior allows the branching degree and molecular weight of polyethylene to be regulated by adjusting the catalyst ligand structure, polymerization temperature and pressure, thereby obtaining polyethylene that is more easily polar grafted, reducing the occurrence of side reactions, and having high adjustability;
[0057] (5) The preparation method of the supported late transition metal catalyst for ethylene polymerization and in-situ grafting provided by the present invention is simple, the catalyst particles have good morphology, the particle size can be adjusted within a large range, and the particle size distribution is narrow. The catalyst particle size can be adjusted according to the use requirements, so that the particle size of the polyethylene powder is reduced, thereby improving the grafting rate. DETAILED DESCRIPTION
[0058] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0059] The test instruments and test conditions used in the examples are as follows:
[0060] Determination of grafting rate (DG): Take 0.5g grafted sample, heat to reflux, dissolve in 70mL xylene, add 15mL KOH-methanol standard solution while hot, continue to reflux for 2h, add 2 drops of phenolphthalein reagent, titrate with standard HCl-isopropanol solution, and titrate the blank sample at the same time to calculate the grafting rate. It is calculated as the mass of maleic anhydride per 100g sample.
[0061] Determination of gel content (DC): A small amount of grafted sample is placed in a filter cloth bag, placed in a Soxhlet extractor, and refluxed with xylene for more than 12 hours. Then the filter cloth bag is taken out and dried in an oven at 80°C until the mass is constant. DC is calculated as the mass (g) of gel in 100g of sample, see formula (1).
[0062] DC = (m3-m2) / (m1-m2) (1)
[0063] In the formula: m1 is the mass of the filter cloth bag after loading the sample, g; m2 is the mass of the filter cloth bag, g; m3 is the total mass after extraction and drying, g.
[0064] Particle size and particle size distribution: The particle size and particle size distribution of the catalyst were tested using a Malvern MS3000 laser particle size distribution analyzer;
[0065] Metal content: The metal content in the catalyst was tested using an inductively coupled plasma mass spectrometer ICP-MS (Agilent 7500CX).
[0066] Determination of initiator content in the catalyst: Liquid nuclear magnetic resonance (Bruker AVANCE 300) was used for determination with hydroquinone as the internal standard.
[0067] Density test: gradient tube method, test method is GB1033BHU.
[0068] The sources of the raw materials used in the examples are as follows:
[0069] Synthesis of late transition metal catalyst 1:
[0070] 7.4 mmol of acenaphthenequinone was heated to reflux in 65 mL of acetonitrile for 30 minutes, 12 mL of formic acid was added to the reaction solution, and the mixture was heated to reflux until all acenaphthenequinone was dissolved. Then 16 mmol of 2,6-diethylaniline / 2,6-dimethylaniline was added, and the mixture was heated to reflux for 3 hours. After the reaction was completed, the reaction solution was cooled to room temperature, concentrated, and recrystallized with hexane to obtain an orange-red solid with a yield of 88%. The product was dried.
[0071] The obtained ligand and an equimolar amount of (DME)NiBr2 were added into a Schlenk bottle with dichloromethane as solvent and stirred at room temperature for 12 hours. After the reaction solution was concentrated, it was recrystallized with ether or hexane to obtain the nickel complex with a yield of 80%.
[0072]
[0073] Late transition metal catalysts 1
[0074] Synthesis of late transition metal catalyst 2:
[0075] According to the synthesis steps of the late transition metal catalyst 1, 2,6-diethylaniline is replaced by 2,4,6-dimethylaniline to obtain the late transition metal catalyst 2.
[0076]
[0077] Late transition metal catalysts 2
[0078] Other raw materials used in the embodiments of the present invention are all commercially available commodities.
[0079] Example 1
[0080] 1. Preparation of supported catalyst: Under nitrogen protection, 6.0g benzoyl peroxide, 0.66g late transition metal catalyst 1 and 40mL 1mol / L sesquiethylaluminum chloride hexane solution were dissolved in 100mL dichloromethane at room temperature. After dissolution, 6g silica (particle size 0.01-2μm) was added and stirred for 2h. Then spray drying was performed using a spray dryer. Spray conditions: inlet temperature: 70℃, outlet temperature 40℃, control the inlet nitrogen flow rate to 31.0m3 / h, and 12.2 g of catalyst was obtained. Some of its physical property parameters are shown in Table 1.
[0081] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst (i.e., supported catalyst) were added, ethylene was added to 1.03MPa, the temperature was raised to 50°C, and the reaction was carried out at a constant temperature and pressure of 50°C for 1h, then the ethylene in the kettle was replaced with nitrogen, and the pressure was raised to 2MPa, and then 6.0g methacrylic acid was added, the temperature was raised to 130°C, and the reaction was carried out for 5h before cooling and discharging. The assessment results are shown in Table 2.
[0082] Example 2
[0083] 1. Preparation of supported catalyst: Under nitrogen protection, 6.0g benzoyl peroxide, 1.32g late transition metal catalyst 1 and 60mL 1mol / L sesquiethylaluminum chloride hexane solution were dissolved in 100mL dichloromethane at room temperature. After dissolution, 6.0g silicon dioxide (particle size of 0.01-2μm) was added and stirred for 2h. Then spray drying was performed using a spray dryer. Spray conditions: inlet temperature: 70℃, outlet temperature 41℃, control the inlet nitrogen flow rate to 31.0m 3 / h, and 12.6g of catalyst was obtained. Some of its physical property parameters are shown in Table 1.
[0084] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C for 45 minutes, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 8.0g methyl methacrylate was added, the temperature was raised to 130°C, and the reaction was continued for 5 hours before cooling and discharging. The assessment results are shown in Table 2.
[0085] Example 3
[0086] 1. Preparation of supported catalyst: Under nitrogen protection, 3.0 g of azobisisobutyronitrile, 1.22 g of late transition metal catalyst 2 and 50 mL of 10% methylaluminoxane dichloromethane solution were dissolved in 100 mL of dichloromethane at room temperature. After dissolution, 3.0 g of silicon dioxide (particle size of 0.01-2 μm) was added and stirred for 2 h. Then spray drying was performed using a spray dryer. Spray conditions: inlet temperature: 70 ° C, outlet temperature 40 ° C, control the inlet nitrogen flow rate at 25.0 m 3 / h, and 8.1 g of catalyst was obtained.
[0087] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C for 1h, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 6.0g diethyl maleate was added, the temperature was raised to 130°C, and the reaction was continued for 5h before cooling and discharging. The assessment results are shown in Table 2.
[0088] Example 4
[0089] 1. Preparation of supported catalyst: Under nitrogen protection, 6.0 g of azobisisobutyronitrile, 0.61 g of late transition metal catalyst 2 and 30 mL of 10% methylaluminoxane dichloromethane solution were dissolved in 100 mL of dichloromethane at room temperature. After dissolution, 6.0 g of silicon dioxide (particle size of 0.01-2 μm) was added and stirred for 2 h. Then spray drying was performed using a spray dryer. Spray conditions: inlet temperature: 70 ° C, outlet temperature 45 ° C, control the inlet nitrogen flow rate at 25.0 m 3 / h, obtaining 12.5g of catalyst.
[0090] 2. Ethylene slurry polymerization and grafting reaction: 1L hexane was added to a 2L polymerization kettle that was purged with nitrogen first and then hydrogen, and 1mL triethylaluminum (1M) and 100mg dry powder catalyst were added at the same time. Ethylene was added to 1.03MPa, and the temperature was raised to 50°C. After reacting at 50°C for 45 minutes, the ethylene in the kettle was replaced with nitrogen and the pressure was raised to 2MPa. Then 8.0g diethyl maleate was added, the temperature was raised to 130°C, and the reaction was continued for 5 hours before cooling and discharging. The assessment results are shown in Table 2.
[0091] Example 5
[0092] The catalyst was prepared according to the method of Example 1, except that during spray drying, the inlet nitrogen flow rate was controlled at 20.0 m 3 / h, and 8.1g of catalyst was obtained. Some of its physical property parameters are shown in Table 1.
[0093] Ethylene slurry polymerization and grafting reaction were carried out according to the method of Example 1 to obtain product samples. The evaluation results are shown in Table 2.
[0094] Comparative Example 1
[0095] In a stainless steel jacketed heating belt stirring reactor, 50g of high-density polyethylene, 4g of methacrylic acid, 4g of benzoyl peroxide and an appropriate amount of interfacial wetting agent were added, the reaction temperature was set to 110°C, and the material was discharged after reacting for 3h, and then washed with xylene and anhydrous ethanol, filtered and dried to obtain a product sample. Its physical properties are shown in Table 2.
[0096] Comparative Example 2
[0097] In a stainless steel jacketed heating belt stirring reactor, 50g of high-density polyethylene, 4g of methacrylic acid, 4g of azobisisobutyronitrile and an appropriate amount of interfacial wetting agent were added, the reaction temperature was set to 110°C, and the material was discharged after reacting for 3h, and then washed with xylene and anhydrous ethanol, filtered and dried to obtain a product sample. Its physical properties are shown in Table 2.
[0098] Comparative Example 3
[0099] The catalyst was prepared according to the method of Example 1, except that benzoyl peroxide was not added, and 11.7 g of supported late transition metal catalyst was obtained. Some of its physical property parameters are shown in Table 1.
[0100] Ethylene slurry polymerization and grafting reaction were carried out according to the method of Example 1, except that the polymerization reaction time was 45 minutes. During the grafting reaction, 6 g of benzoyl peroxide was added at the same time as methacrylic acid to obtain a product sample. The evaluation results are shown in Table 2.
[0101] Table 1. Physical parameters of supported transition metal catalysts
[0102]
[0103]
[0104] Table 2. Some physical properties of grafted polyethylene
[0105]
[0106] It can be seen from the data in Table 1 that the metal loading and free radical content of the supported late transition metal catalysts for ethylene polymerization and in-situ grafting obtained in Examples 1 to 4 of the present invention can be adjusted according to the formula, and the particle size can be regulated by the slurry formula and process conditions, so that smaller polyethylene particles can be obtained, which is more conducive to improving the grafting reaction rate and has a narrower particle size distribution.
[0107] In Example 5, the catalyst size becomes larger by changing the spray drying conditions (Table 1), and the polymer particle size obtained by such a catalyst also becomes larger. Compared with Example 1, it can be seen that Example 5 reduces the grafting efficiency, indicating the controllability of the catalyst particle size.
[0108] It can be seen from the data in Table 2 that the initiator content in Examples 1 to 4 is much lower than that in the comparative example, so the gel content of the obtained product is low, and the late transition metal catalyst has a "chain walking" effect, and branched polyethylene can be obtained without adding a comonomer, which is easier to initiate the second step of grafting reaction and improve the grafting efficiency; under the condition of less initiator and polar monomer dosage, a one-step method can be used to directly obtain a polar grafted polyethylene with a higher grafting rate and a lower gel rate; the obtained polymer does not need to be dried and separated, the preparation process is short, and due to the advantages of the catalyst and the polymer preparation method, the polymer has a higher bulk density.
[0109] The other conditions of Comparative Example 3 are the same as those of Comparative Example 1, but the initiator is not in the catalyst but added during the grafting reaction. Thus, the initiator cannot be uniformly introduced into the polymer during the first polymerization reaction, resulting in low grafting efficiency (Table 2), indicating that adding the initiator to the catalyst and uniformly dispersing it in the polymer through the polymerization reaction achieves an unexpected technical effect.
[0110] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
[0111] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.
[0112] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.
[0113] The endpoints and any values of the scope disclosed in the present application document are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, between the endpoint values of each scope, between the endpoint values of each scope and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be considered as specifically disclosed in this article.
[0114] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.
[0115] Moreover, any embodiment described in this document may be freely combined with one or more other embodiments described in this document, and the technical solutions or technical ideas formed thereby are deemed to be part of the original disclosure or original record of the present invention, and should not be regarded as new content that has not been disclosed or anticipated in this document, unless a person skilled in the art considers that the combination is obviously unreasonable.
Claims
1. A supported late transition metal catalyst comprising a blended component and / or reaction product of the following raw materials: a carrier, a late transition metal catalyst, an activator and a free radical initiator, The activator is an organic aluminum compound.
2. The supported late transition metal catalyst according to claim 1, characterized in that The carrier is selected from inorganic oxide carriers, preferably silicon oxide and / or aluminum oxide, more preferably silicon dioxide; and / or, The particle size of the carrier is 0.01 to 5 μm, preferably 0.01 to 2 μm.
3. The supported late transition metal catalyst according to claim 1, characterized in that The free radical initiator is selected from at least one of azo and peroxide initiators, preferably selected from at least one of benzoyl peroxide, diisopropylbenzene peroxide, di-tert-butyl peroxide, tert-butyl hydroperoxide, tert-butyl perbenzoate, diisobutyl peroxydicarbonate, azobisisobutyronitrile and azobisisoheptylonitrile.
4. The supported late transition metal catalyst according to claim 1, characterized in that The organoaluminum compound is AlR n X (3-n) or contains A compound of the structure, wherein R is an alkyl group having 1 to 10 carbon atoms, X is a halogen, and n is an integer of 1 to 3; preferably, The organoaluminum compound is at least one selected from trimethylaluminum, triethylaluminum, methylaluminoxane, diethylaluminum monochloride, ethylaluminum dichloride, tri-n-butylaluminum, triisobutylaluminum, sesquimethylaluminum chloride, and sesquiethylaluminum chloride.
5. The supported late transition metal catalyst according to claim 1, characterized in that The late transition metal catalyst has a structure as shown in formula (I): In formula (I), R1 to R2 are each selected from hydrogen or an alkyl group or an aryl group having 1 to 20 carbon atoms, preferably each selected from at least one of hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms; R3 to R8 are each selected from hydrogen or an alkyl or aryl group having 1 to 20 carbon atoms, preferably each selected from at least one of hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms; X1 and X2 are halogen, preferably each selected from at least one of chlorine, bromine and iodine; M is Fe, Co or Ni.
6. The supported late transition metal catalyst according to any one of claims 1 to 5, characterized in that Based on the total mass of the supported late transition metal catalyst as 100wt%, the content of the late transition metal element M in the supported late transition metal catalyst is 0.1-5wt%, preferably 0.3-3wt%, and / or the content of the free radical initiator is 10-60wt%, preferably 20-40wt%; and / or, The molar ratio of aluminum to the late transition metal M in the organic aluminum compound is (5-500):1, preferably (20-200):
1.
7. The supported late transition metal catalyst according to any one of claims 1 to 5, characterized in that The average particle size of the supported late transition metal catalyst is 7 to 100 μm, preferably 8 to 30 μm; and / or, The particle size distribution of the supported late transition metal catalyst is less than 2, preferably less than 1.
5.
8. A method for preparing the supported late transition metal catalyst according to any one of claims 1 to 7, comprising the following steps: (1) dispersing components including the late transition metal catalyst, an activator, a carrier, and a free radical initiator in an organic solvent to form a slurry; (2) spray drying the slurry obtained in step (1) to obtain the supported late transition metal catalyst; preferably, The preparation of the slurry in step (1) comprises: dissolving a free radical initiator, a late transition metal catalyst, and an activator in an organic solvent and then adding a carrier; more preferably, first dissolving the free radical initiator, the late transition metal catalyst, and the activator in an organic solvent, adding the carrier at 20 to 45° C. and mixing for 2 to 12 hours; and / or, The spray drying conditions in step (2) are: inlet temperature 50-200° C., outlet temperature 30-150° C.; and / or, The air flow rate of the spray drying nozzle in step (2) is 10-50m 3 / h.
9. The preparation method according to claim 8, characterized in that: The organic solvent is selected from at least one of alkanes, halogenated alkanes, aromatic hydrocarbons, heterocyclic compounds, ethers, ketones, and esters, preferably selected from at least one of pentane, hexane, heptane, dichloromethane, chloroform, benzene, toluene, chlorobenzene, chlorotoluene, tetrahydrofuran, acetone, ether, and ethyl acetate; and / or, The amount of the organic solvent used is 5 to 100 mL, preferably 10 to 50 mL, relative to 1 g of the carrier.
10. The preparation method according to claim 8 or 9, characterized in that: In parts by mass, relative to 1 part of the carrier, the amount of the late transition metal catalyst is 0.01-1 part, the amount of the activator is 0.1-30 parts, and the amount of the free radical initiator is 0.02-10 parts; preferably, In parts by mass, relative to 1 part of the carrier, the amount of the late transition metal catalyst is 0.05-0.5 parts, the amount of the activator is 0.3-10 parts, and the amount of the free radical initiator is 0.1-3 parts.
11. Use of the supported late transition metal catalyst according to any one of claims 1 to 7 or the supported late transition metal catalyst prepared by the preparation method according to any one of claims 8 to 10 in olefin polymerization.
12. The use according to claim 11, characterized in that: The application of the supported late transition metal catalyst in olefin polymerization includes: 1) contacting ethylene with the supported late transition metal catalyst to perform ethylene polymerization reaction to obtain polyethylene powder containing a free radical initiator; 2) contacting the polar monomer with the polyethylene powder containing the free radical initiator obtained in 1) so that the free radical initiator initiates in-situ grafting of the polar monomer on the polyethylene; preferably, The polar monomer is a compound containing a double bond and a polar group, and more preferably at least one of acrylic acid and its derivatives or esters, maleic anhydride or esters, maleate, alkenyl bisphenol A ether, acrylonitrile, styrene and its homologues, and glycidyl methacrylate.
Citation Information
Patent Citations
A kind of supported late transition metal catalyst for ethylene polymerization, preparation method and application
CN104059175B
Diamine ligand, diamine coordination compound, catalyst containing diamine coordination compound
CN111116787A
Diimine metal complex and preparation method and application thereof
CN112745362A
Post-transition metal catalyst for olefin polymerization and preparation method and application thereof
CN114478868A
Late transition metal double-peak catalyst for ethane polymerization, preparation method and uses thereof
CN101225129A